I am trying to break your heart [videorecording (DVD)] - Jones, Sam, 1966-; Tweedy, Jeff, 1967-; Stirratt, John; Bach, LeRoy; Kotche, Glenn; Bennett, Jay, 1963-2009 (Plexigroup, 2006)
Building on three critically acclaimed records and a reputation for phenomenal live shows, the band seemed poised to cement its reputation as one of the great American rock groups. So how is it that one year later, with completed record in hand, the band found itself rejected by its corporate record label and missing two of its original members? Filmmaker Sam Jones was on hand, chronicling this turbulent chapter in Wilco's history as it unfolded.